(untitled) (Jurnal Orthopaedagogia, 2025)
Mapping working-age persons with disabilities at the city level—together with their vocational training interests—is a prerequisite for designing targeted interventions. However, operational data that integrate disability profiles with training preferences in Magelang City remain scattered. This study aimed to map the profile of working-age persons with disabilities in Magelang City and to map relevant vocational training interests. This research used a descriptive survey of working-age persons with disabilities (≥15 years) listed by local stakeholders (n = 257). The main variables were disability types and training interest/history. Analysis was descriptive, presented in tables with narrative explanations. The results showed that the largest disability groups were intellectual disability (24.90%) and physical disability (24.90%), followed by psychosocial disability (19.46%) and multiple disabilities (14.01%). Training interest was dominated by the “other/self-employed” category (69.60%), pointing to home-based microenterprise, followed by cooking (6.20%) and batik (5.40%). The needs map indicates a strong preference for adaptive, home-based training alongside selected technical skills. These findings underline the importance of modular curricula, capacity-building for inclusive trainers, and stronger placement/market partnerships for wage work or microenterprise.